1988
DOI: 10.1017/s0305000900012435
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of the meanings of modality in children aged eight and twelve

Abstract: Little is known about children's acquisition of modality. It seems clear that at the age of five, when they are said to be linguistically competent, children have not mastered the adult system of modal meaning. This paper describes research which tests children's understanding of modal meaning at the ages of eight and twelve. The results of these tests are compared with the results of the same test on adult informants. The research uses the card-sorting method devised by Miller (1971) to investigate semantic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 2 publications
0
16
0
1
Order By: Relevance
“…Coates (1988) observed that a linguistically competent five-year-old still does not have an adult's system of modals; a cultivation of the logical component may well be critical to progress with modals. In the test of relative force in Experiment i, five-year-olds' performance generally revealed that they appreciate distinctions in relative force among the terms is, has to and might.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coates (1988) observed that a linguistically competent five-year-old still does not have an adult's system of modals; a cultivation of the logical component may well be critical to progress with modals. In the test of relative force in Experiment i, five-year-olds' performance generally revealed that they appreciate distinctions in relative force among the terms is, has to and might.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an investigation of modal comprehension Coates (1988) showed that eight-and twelve-year-old children employ the modal might in an adult-like manner. One is that recorded modal uses may reflect the situations in which children tend to find themselves and not necessarily their progressive mastery of the studied terms.…”
mentioning
confidence: 99%
“…Coates (1988) found that even by the age of 12, children's categorization of modal terms was not yet isomorphic with that of adults.…”
Section: How Do People's Deontic Capabilities Develop?mentioning
confidence: 97%
“…Finally, from developmental studies we know that deontic capabilities are not available ''in one block'' at a certain age as the evolutionary view might suggest. Instead, the full comprehension of the deontic system is the result of language acquisition processes that take several years (e.g., Bascelli & Barbieri, 2002;Hirst & Weil, 1982) and is not yet finished at the age of twelve (Coates, 1988).…”
Section: Discussionmentioning
confidence: 99%